2002
DOI: 10.1021/ie0107789
|View full text |Cite
|
Sign up to set email alerts
|

Terephthalic Acid Synthesis in High-Temperature Liquid Water

Abstract: We have completed an exploratory study of the synthesis of terephthalic acid via the partial oxidation of p-xylene in liquid water at temperatures ranging from 250 to 350°C. The reactions occurred in 1.54 mL stainless steel batch reactors, and the batch holding time was 60 min. We determined the influence of temperature, catalyst identity, p-xylene initial concentration, and oxidant initial concentration on the yield of terephthalic acid and intermediate products. The catalysts included in this study were mang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 7 publications
2
43
0
Order By: Relevance
“…We analyzed both the products in the batch reactor after the reaction and those in the sample bulbs via HPLC using a method described previously. 6 This HPLC analysis provides the concentration of each compound, which then admits calculation of product selectivity and yield. The volume of the sample bulb plus material purged during sampling (3.2 mL) was small in comparison with that of the batch reactor (440 mL), so ;90 mol % of the initial material added to the reactor should remain within it at the end.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed both the products in the batch reactor after the reaction and those in the sample bulbs via HPLC using a method described previously. 6 This HPLC analysis provides the concentration of each compound, which then admits calculation of product selectivity and yield. The volume of the sample bulb plus material purged during sampling (3.2 mL) was small in comparison with that of the batch reactor (440 mL), so ;90 mol % of the initial material added to the reactor should remain within it at the end.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Our group has reported on p-xylene partial oxidation in HTW and found that the highest TPA yields ([80 mol %) were obtained at 3008C, [ , and t 5 5-15 min. 5 Moreover, under these conditions and t 5 15 min, the yields of carbon monoxide and carbon dioxide, which are products from burning, were below 2%.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that benzyl bromide, acting as a byproduct, had no activity in Co/Mn/Br catalyst oxidation. 20 As shown in eq 3, a suitable amount of water could hydrolyze benzyl bromide to a release of active bromine. (3) That is, higher AA concentration could inhibit hydrolysis of benzyl bromide and thus cause more bromine to exist in benzyl bromide.…”
Section: Methodsmentioning
confidence: 99%
“…The use of either supercritical or high-temperature liquid water as a benign substitute for acetic acid has been reported [75][76][77][78]. The reaction systems were necessarily operated at high temperatures (330-450 °C) and high pressures (250-270 bar) with TPA yields of >90%.…”
Section: Alternative Solventmentioning
confidence: 99%